Clinical Anatomy and Significance of the Retromolar Foramina and Their Canals: A Literature Review - Truong, Mindy K (Cureus, 2017)
The retromolar foramina (RMF) and the retromolar canal (RMC) are anatomic variants in the mandible located distally to the last molar. The retromolar nerve, which runs through the RMC, is a type 1 bifidity of the mandibular canal. The investigations of the RMF and RMC have been performed by dry mandible studies, the panoramic radiograph (PAN), computed tomography (CT), and the cone beam computed tomography (CBCT) studies. The CBCT has been shown to be the superior method for visualizing the RMF and RMC. There is wide variation in the frequency, location, diameter, and distance of the canal in different individuals. Overall, there is no significant difference in the frequency of the canal in the mandible between sexes or sides of the mandible. The peak incidence of the RMF may occur in adolescence. The RMC is significant due to the neurovascular bundle which runs through it. Injury to this neurovascular bundle during surgical procedures, such as third molar extraction, implant placement, or split sagittal osteotomy, may lead to paresthesia, excessive bleeding, or traumatic neuroma. The presence of RMC may also lead to insufficient anesthesia in the mandible which may be overcome with alternative anesthetic techniques.